RNA processing and decay in plastids. (27th March 2013) - Germain, Arnaud; Hotto, Amber M.; Barkan, Alice; Stern, David B.
Abstract Plastids were derived through endosymbiosis from a cyanobacterial ancestor, whose uptake was followed by massive gene transfer to the nucleus, resulting in the compact size and modest coding capacity of the extant plastid genome. Plastid gene expression is essential for plant development, but depends on nucleus‐encoded proteins recruited from cyanobacterial or host‐cell origins. The plastid genome is heavily transcribed from numerous promoters, giving posttranscriptional events a critical role in determining the quantity and sizes of accumulating RNA species. The major events reviewed here are RNA editing, which restores protein conservation or creates correct open reading frames by converting C residues to U, RNA splicing, which occurs both in cis and trans, and RNA cleavage, which relies on a variety of exoribonucleases and endoribonucleases. Because the RNases have little sequence specificity, they are collectively able to remove extraneous RNAs whose ends are not protected by RNA secondary structures or sequence‐specific RNA‐binding proteins (RBPs). Other plastid RBPs, largely members of the helical‐repeat superfamily, confer specificity to editing and splicing reactions. The enzymes that catalyze RNA processing are also the main actors in RNA decay, implying that these antagonistic roles are optimally balanced. We place the actions of RBPs and RNases in the context of a recent proteomic analysis that identifies components of the plastid nucleoid, a protein–DNA complex with multiple roles in gene expression. These results suggest that sublocalization and/or concentration gradients of plastid proteins could underpin the regulation of RNA maturation and degradation. WIREs RNA 2013, 4:295–316. doi: 10.1002/wrna.1161 For further resources related to this article, please visit the WIREs website. The authors have declared no conflicts of interest for this article.